A secondary dengue 4 infection in a traveler returning from Haiti confirmed by virus isolation, complete genome sequencing and neutralisation assay: A brief report. Issue 1 (January 2015) - Menard, Amelie; Ninove, Laetitia; Zandotti, Christine; Leparc-Goffart, Isabelle; Klitting, Raphaelle; Baronti, Cecile; Stein, Andreas; de Lamballerie, Xavier; Charrel, Rémi N.
Summary: Here we report the clinical and laboratory findings of a dengue 4 virus (DENV) secondary infection in a patient returning from Haiti to France. The diagnostic of acute DEN-4 virus infection was demonstrated by (i) the presence of DEN-4 RNA in two successive serum samples, (ii) the isolation of a DEN-4 virus in Vero cells and subsequent identification of subtype IIb through complete genome sequencing, (iii) the presence of dengue NS1 antigen, (iv) the seroconversion with detection of dengue IgM in the second serum while negative in the first serum. The diagnosis of secondary dengue episode was demonstrated by (i) the presence of dengue IgG in the early serum, and (ii) the demonstration that neutralising antibodies against DEN-3 were present at the acute stage of the disease. Next-generation sequencing has a primary role to play in phylogeographic studies including database sequences, sequences from imported cases, and sequences from autochthonous cases.